Hybrid Real-Time Simulator for Setting of Automatic Secondary Frequency and Active Power Control; EEA - Electrotehnica, Electronica, Automatica; Vol. 68, iss. 2 - Ufa R. A. Ruslan Alexandrovich; Vasilev A. S. Alexey Sergeevich; Ruban N. Yu. Nikolay Yurievich; Rudnik V. E. Vladimir Evgenevich (2020, 2020)
Title screen